Forecasting the Unit Price of Water and Wastewater Pipelines Capital Works and Estimating Contractors' Markup. Issue 1 (2nd January 2016) - Younis, Rizwan; Rehan, Rashid; Unger, Andre J. A.; Yu, Soonyoung; Knight, Mark A.
Abstract : Municipalities and water utilities need to make realistic estimates for the replacement of their aged water and wastewater pipelines. The two main objectives of this article are to present a method to forecast the unit price of water and wastewater pipelines capital works by investigating inflation in their construction price, and to quantify the markup that contractors add to bid a project price. The Geometric Brownian Motion model with drift is used for investigation. Results show that the inflation in water and wastewater pipelines reference projects were 6.41% and 5.52% per annum, respectively. These values compare to the inflation in the Standard & Poor's/Toronto Stock Exchange (S&P/TSX) Composite Index of 6.93% per annum. In contrast, inflation in Canada's Consumer Price Index (CPI), and Engineering News-Record's Construction Cost Index (ENR's CCI) for Toronto are estimated to be 2.53% and 2.85% per annum, respectively. The spread in the inflation rate between the reference price indices and that of either ENR's CCI or CPI is a measure of the market price of catchall financial premium (defined as markup) that contractors add to project cost to account for profit, risk, and market conditions. This spread is estimated to be 3.56% and 2.67% per annum for water and wastewater pipeline capital works, respectively.